(untitled) (Praxis Educativa, 2026)
This article presents a comprehensive pedagogical proposal to transform the teaching of social sciences from a decolonial perspective through the conceptual framework Walking Decolonial Teaching. The proposal articulates four interdependent dimensions (ontological-political, epistemic, relational, and socio-affective-spiritual) with five progressive pedagogical phases (naming, making, making visible, understanding, imagining, and creating) that configure the decolonial footprint. Seven existential dimensions (being, dwelling, gazing, thinking, listening, feeling, and co-living) are developed to traverse the entire educational experience. The proposal has materialized in three specific didactic units: Territories and Memories (Cycle III), Other Economies (Cycle IV), and Insurgent Citizenships (Cycle V), designed through pedagogical progression patterns that move from the near to the distant, from the personal to the collective, and from denunciation to transformative proposals. The document positions pedagogical re-existence as a horizon for collective transformation that seeks to fracture colonial structures from the classrooms and territories of Our America (NuestrAmérica).